Malassezia yeasts produce a collection of exceptionally potent activators of the ah (dioxin) receptor detected in diseased human skin - Magiatis, P.a b; Pappas, P.c; Gaitanis, G.d; Mexia, N.a; Melliou, E.a e; Galanou, M.c; Vlachos, C.c d; Stathopoulou, K.a; Skaltsounis, A.L.a; Marselos, M.c; Velegraki, A.f; Denison, M.S.b; et al. (Journal of Investigative Dermatology, 2013)
Malassezia yeasts are commensal microorganisms, which under insufficiently understood conditions can become pathogenic. We have previously shown that specific strains isolated from diseased human skin can preferentially produce agonists of the aryl hydrocarbon receptor (AhR), whose activation has been linked to certain skin diseases. Investigation of skin scale extracts from patients with Malassezia-associated diseases demonstrated 10-to 1,000-fold higher AhR-activating capacity than control skin extracts. Liquid chromatography-tandem mass spectrometry analysis of the patients’ extracts revealed the presence of indirubin, 6-formylindolo[3,2-b]carbazole (FICZ), indolo[3,2-b]carbazole (ICZ), malassezin, and pityriacitrin. The same compounds were also identified in 9 out of 12 Malassezia species culture extracts tested, connecting their presence in skin scales with this yeast. Studying the activity of the Malassezia culture extracts and pure metabolites in HaCaT cells by reverse transcriptase real-time PCR revealed significant alterations in mRNA levels of the endogenous AhR-responsive genes Cyp1A1, Cyp1B1, and AhRR. Indirubin-and FICZ-activated AhR in HaCaT and human HepG2 cells with significantly higher, yet transient, potency as compared with the prototypical AhR ligand, dioxin. In loco synthesis of these highly potent AhR inducers by Malassezia yeasts could have a significant impact on skin homeostatic mechanisms and disease development. © 2013 The Society for Investigative Dermatology.
cited By (since 1996)2
Keywords: aromatic hydrocarbon receptor; article; Aryl Hydrocarbon; Carcinoma; Cell Extracts; Cell Line; concentration response; controlled study; Cytochrome P-450 CYP1A1; cytochrome P450 1A1; cytochrome P450 1B1; Dermatomycoses; disease course; fungus culture; Hepatocellular; high performance liquid chromatography; homeostasis; human; human cell; human tissue; Humans; indirubin; Indoles; keratinocyte; Keratinocytes; liquid chromatography; Liver Neoplasms; Malassezia; Malassezia folliculitis; Malassezia furfur; Messenger; Messenger RNA; nonhuman; priority journal; real time polymerase chain reaction; Receptors; reverse transcription polymerase chain reaction; RNA; seborrheic dermatitis; skin; skin disease; tandem mass spectrometry; Transformed; Tumor; yeast